Evaluation of formal educational processes for healthcare professionals - Eloá Otrenti; Vera Lúcia Mira; Sarah Marília Bucchi; Jairo Eduardo Borges-Andrade (Universidad de Antioquia, 2014)
Objective. Analyzing the scientific literature on the evaluation of formal educational processes for healthcare professionals. Methodology. Integrative literature review in which were reviewed the following databases: VHL, Pubmed and Cochrane. The final sample was composed of 19 articles in Portuguese, English and Spanish published from 2000 to July 2010. The subject of study was the evaluation of formal educational processes for health professionals, which had at least the abstract available online. Results. There is no use of a systematic methodology to evaluate the formal educational processes in this study group. The evaluation focus mainly on the learning of participants, with little attention to the teaching process. There are no evaluations on the impact caused by this type of training in institutions and users of the health system, which can incur the risk of reducing the value of formal education processes. Conclusion. A full evaluation of the formal educational processes for professionals during a longer time is important to assess the impact of these processes and provide information about the necessities of continuing education of this population.